Possibilidades de adoção do reflorestamento pelos agricultores em diferentes níveis de ajuda financeira - Moreira Ferreira da Silva , Sebastião (Revista Ceres, 2025)
The objective of the present researck was to examine the possibility of adoption of reforestation by land-owners with levels of financial assistance substantially below those projects carried out under the policy of governamental fiscal incentives. Based on the results this study, it was observed that lack of capital constituted the principal obstacle to the adoption of reforestation by the land-owners interviewed, and that these land-owners could reforest with relatively lettle financial help with large economic and social effects.